Roles of contrast-enhanced ultrasonography in identifying volume change of benign thyroid nodule and optical time of secondary radiofrequency ablation - Ziyu Jiao (BMC Medical Imaging, 2020)
Abstract Background Ultrasonography-guided radiofrequency ablation (RFA) was was proved to be an effective and safe treatment with few complications for benign thyroid nodule. In cases of incompletely treated nodule margin, secondary RFAs are necessary. The present study was designed to analyze the dynamic change of nodular volume of benign thyroid tumors accessed using contrast-enhanced ultrasonography (CEUS) after RFA, and hopefully to offer evidence for time decision of secondary RFA. Methods A total of 105 patients who received ultrasonography-guided RFA in the Department of Ultrasound, Chinese PLA General Hospital between April 2014 and August 2018 for benign thyroid nodule were enrolled in this retrospective study. Vt increase (regrowth) and vital volume (Vv) of thyroid nodule were followed up at 0, 1, 3, 6, 12, 24 and 36 months after RFA. Results A total of 105 nodules of 105 patients were enrolled in the present study, with a mean age of 46.70 ± 13.05 years, and 87 of them (82.9%) were female. The median follow up time was 25.1 months (12 months to 36 months). During the follow up, regrowth occurred in 43 cases, 95.35% of nodular regrowth occurred in 12 months after RFA, and the rate showed substantial consistency with that on the 36th month postoperatively (Kappa = 0.656). Conclusions CEUS was an effective and safe tool to monitor volume change of benign thyroid nodules after RFA. The majority cases of regrowth occurred in 12 months after RFA, thus, the 12th month after RFA might be the optimal time for volume assessment to make the decision of secondary RFAs.